Circadian-Like Rhythmicity of Extracellular Brain Glutamate in Epilepsy - Sandhu, Mani Ratnesh S.; Dhaher, Roni; Gruenbaum, Shaun E.; Raaisa, Raaisa; Spencer, Dennis D.; Pavlova, Milena K.; Zaveri, Hitten P.; Eid, Tore (Frontiers in Neurology, 2020)
Seizures often exhibit striking circadian-like (~24-h) rhythms. While chronotherapy has shown promise in treating epilepsy, it is not widely used, in part because the patterns of seizure rhythmicity vary considerably among patients and types of epilepsy. A better understanding of the mechanisms underlying rhythmicity in epilepsy could be expected to result in more effective approaches which can be tailored to each individual patient. The excitatory neurotransmitter glutamate is an essential modulator of circadian rhythms, and changes in the extracellular levels of glutamate likely affect the threshold to seizures. We used a reverse translational rodent model of mesial temporal lobe epilepsy (MTLE) combined with long-term intracerebral microdialysis to monitor the hourly concentrations of glutamate in the seizure onset area (epileptogenic hippocampus) over several days. We observed significant 24-h oscillations of extracellular glutamate in the epileptogenic hippocampus (n = 4, JTK_CYCLE test, p < 0.05), but not in the hippocampus of control animals (n = 4). To our knowledge, circadian glutamate oscillations have not been observed in a seizure onset region, and we speculate that the oscillations contribute to the rhythmicity of seizures in MTLE.